Immunological findings in psychotic syndromes: a tertiary care hospital's CSF sample of 180 patients - Endres, Dominique; Perlov, Evgeniy; Baumgartner, Annette; Hottenrott, Tilman; Dersch, Rick; Stich, Oliver; Tebartz Van Elst, Ludger (Frontiers in Human Neuroscience, 2015)
Immunological mechanisms and therapy approaches in psychotic syndromes were recently supported by the discovery of autoantibody-associated limbic and non-limbic encephalitis. However, how clinical diagnostic procedures in psychiatry should be adapted to these new insights is still unclear. In this study, we analyzed the cerebrospinal fluid (CSF) and neuroimmunological alterations and their association with cerebral MRI (cMRI) and electroencephalographic (EEG) findings. From 2006 until 2013, we acquired 180 CSF samples from psychotic patients. Between 2006 and 2009, CSF examinations were only performed in cases in which organic brain disease was suspected. Since then, this procedure has been integrated into our routine diagnostic workup. CSF basic diagnostics were supplemented by measuring antineuronal antibodies against intracellular synaptic antigens, antibodies against intracellular onconeural antigens, antibodies against neuronal cell surface antigens and thyroid antibodies. In addition, cMRIs and EEGs were conducted. We found white cell counts elevated in 3.4% of the cases, albumin quotient elevated in 21.8%, and protein concentration elevated in 42.2%. Evidence of intrathecal immunoglobulin synthesis was found in 7.2% of the cases. Antibodies measured against neuronal cell surface antigens were positive in 3.2%. Reactivity on antibodies against intracellular onconeural antigens were detected in 3.5%. Serum thyroid antibodies were elevated in 24.7%. Abnormalities were found in 39.5% of cMRIs and in 34.3% of EEGs. The main finding of our study was the high prevalence of CSF and autoantibody abnormalities in 54.4% of psychotic patients. In combination with cMRIs and EEGs, 75.6% showed abnormal findings. Our results are discussed with regard to the concept of immunological encephalopathy. Future studies should analyze the efficacy of immunomodulatory therapies.